Al-Maqrizi's Inflation Concepts and Proof for the East Java Inflation Case 2015-2020 - Rizqon, Abdul Latif; Prasetya, Teguh Eka; Ramadhan, Mahendra Utama Cahya; Habibah, Shofiyatul (AL- IKTISAB Journal of Islamic Economic Law, 2022)
••• English ••• The standard of individual and collective life in a nation state has become economic life, and inflation is one of present economic problems, particularly in monetary matters. When compared to other provinces in the Java region, East Java had the highest inflation rate. The purpose of this research is to discuss the thinking on inflation in East Java from 2015 to 2020 from Taqiyuddin Abul Abbas Al-Husaini's from Maqorizah, Cairo, or more commonly known as Al-Maqrizi. This research is library research. The method used is a descriptive and inductive analysis method, in which thought is analyzed using data and the role of Al-Maqrizi's thinking on inflation is examined. The analysis indicate that the circulation of money, the existence of state debt, exchange rates, production costs, excessive taxes, corruption, collusion and nepotism, increased currency circulation, and increased demand were the causes of inflation in East Java. This is exactly what Al-Maqrizi says in several parts of his book, which clearly says that inflation is generally divided into two types, natural inflation and human error inflation. Al-Maqrizi's views on inflation in East Java advocated for the government to use the central bank to control the money supply or interest rates as a tool for price control. Furthermore, the central bank is required to control the exchange rate of the domestic currency. Based on this analysis, the researcher advises the East Java government to take precedence an economic step, namely Islamic philanthropy. This Islamic social financial instrument is a component that can provide assistance to economically disadvantaged communities in the short to long term. ••• Indonesian ••• Standar kehidupan individu dan kolektif dalam suatu negara telah menjadi bagian dari kehidupan ekonomi, dan inflasi merupakan salah satu masalah ekonomi saat ini, terutama dalam masalah moneter. Jika dibandingkan dengan provinsi lain di wilayah Jawa, Jawa Timur memiliki tingkat inflasi yang paling tinggi. Tujuan dari penelitian ini adalah untuk membahas pemikiran tentang inflasi di Jawa Timur dari tahun 2015 hingga 2020 dari Taqiyuddin Abul Abbas Al-Husaini dari Maqorizah, Kairo, atau yang lebih dikenal dengan Al-Maqrizi. Penelitian ini merupakan penelitian kepustakaan. Metode yang digunakan adalah metode analisis deskriptif dan induktif, di mana pemikiran dianalisis dengan menggunakan data dan mengkaji peran pemikiran Al-Maqrizi terhadap inflasi. Hasil analisis menunjukkan bahwa peredaran uang, adanya utang negara, nilai tukar, biaya produksi, pajak yang berlebihan, korupsi, kolusi dan nepotisme, peredaran uang yang meningkat, dan permintaan yang meningkat menjadi penyebab inflasi di Jawa Timur. Hal ini persis seperti yang dikatakan Al-Maqrizi dalam beberapa bagian bukunya, yang secara gamblang menyebutkan bahwa inflasi secara umum terbagi menjadi dua jenis, inflasi alamiah dan inflasi kesalahan manusia. Pandangan Al-Maqrizi tentang inflasi di Jawa Timur menganjurkan agar pemerintah menggunakan bank sentral untuk mengendalikan jumlah uang beredar atau suku bunga sebagai alat pengendalian harga. Selanjutnya, bank sentral diharuskan untuk mengontrol nilai tukar mata uang domestik. Berdasarkan analisis tersebut, peneliti menyarankan kepada pemerintah Jawa Timur untuk mengutamakan langkah ekonomi yaitu filantropi Islam. Instrumen keuangan sosial Islam ini merupakan komponen yang dapat memberikan bantuan kepada masyarakat yang kurang mampu secara ekonomi dalam jangka pendek hingga jangka panjang.